(untitled) (Docentes 2.0 Journal, 2020)
Currently, the spread of cell phones, as well as applications for them, have been present in different sectors of society. Among the instant messaging applications, WhatsApp has stood out, which has become part of the daily life of most people who have a cell phone. The research focused on the use of WhatsApp, to know the influence it has among the students at the Autonomous University of Carmen (UNACAR). The objective of this research was to know, first how much they use WhatsApp, and second how much it is useful for their academic activities. A quantitative research was carried out, on an innovative topic that is present in everyday life, the WhatsApp, and its use among higher education students. For the study, a survey was applied to 100 students. The results obtained demonstrated the intensive use of said application. WhatsApp can become an effective communication tool between students and teachers, due to the scope of the use of the tool among people, most have a smartphone, which surely has the WhatsApp application installed, although there will be What to consider that there are other applications that possibly have better functionalities than WhatsApp. Based on the findings of the research carried out, it is concluded that WhatsApp is a widely used tool among higher level students.